Potentials and Challenges of Chinese Foreign Direct Investment in Indonesia - Melda Ria Juwita; Tao Wang; Yusup Gumilar Sukma; Maman Iskandar; Agus Supriyadi (Research Institute and Community Engagement of IAIN MADURA, 2020)
Program ekonomi China Belt and Road Initiatives (BRI) memiliki pengaruh besar pada laju ekonomi dunia, terutama di negara-negara tuan rumah yang berpartisipasi di dalamnya. Indonesia adalah negara yang menjadi bagian dari program ini di kawasan Asia Tenggara, mengalami dampak yang cukup besar dalam hal pembangunan ekonomi dan peningkatan nilai investasi asing, yang ditandai dengan penambahan proyek investasi di berbagai bidang industri. Pertumbuhan investasi asing Cina di Indonesia dapat dilihat dari perkembangan taman industri Cina di beberapa daerah di Indonesia. Artikel ini disusun dengan melakukan tinjauan literatur dan pengumpulan data yang akurat yang bersumber dari Badan Koordinasi Penanaman Modal Indonesia (BKPM) dengan tujuan untuk menganalisis potensi dan tantangan yang muncul dari FDI Tiongkok untuk Indonesia dan sebaliknya. Hasil yang diperoleh dari penelitian ini adalah, terlepas dari potensi pangsa pasar Indonesia karena jumlah penduduk yang besar, kemudahan memperoleh bahan baku untuk produksi dan upah minimum untuk pekerja lokal relatif rendah. Namun, bagi investor Cina, hal ini diikuti oleh tantangan yang juga muncul, seperti harga tanah yang tinggi, infrastruktur Indonesia yang tidak memadai, dan berbagai peraturan investasi di hampir setiap wilayah. Bagi Indonesia, peningkatan FDI Cina mendorong lapangan kerja, memberikan peluang bagi alih teknologi dan pengetahuan. Namun, masalah lain muncul, seperti persaingan untuk pengusaha lokal dan kekhawatiran tentang ketergantungan ekonomi Indonesia pada Cina. Selain itu, untuk mendapatkan pemahaman komprehensif tentang taman Industri Cina dan dampaknya, penelitian masa depan dengan penelitian survei lapangan sangat dianjurkan.(The China Belt and Road Initiatives (BRI) economic program has an enormous influence on the pace of the world economy, especially in host countries that participate in it. Indonesia is a country that is a part of this program in the Southeast Asian region, experienced a considerable impact in terms of economic development and an increase in the value of a foreign investment, which is marked by the addition of investment projects in various fields of industry. The growth of Chinese foreign investment in Indonesia can be seen by the development of Chinese industrial parks in several regions in Indonesia. This article was prepared by conducting a literature review and accurate data collection sourced from the Indonesia Investment Coordinating Board (IICB) with the objectives to analyze the potentials and challenges that arise from Chinese FDI for Indonesia and vice versa. The results obtained from this study are, despite the potential of the Indonesian market share due to the large population, the ease of obtaining raw materials for production and the minimum wage for local workers is relatively low. However, for Chinese investors, it is followed by challenges that also arise, such as high land prices, inadequate Indonesian infrastructure, and different investment regulations in almost every region. For Indonesia, an increase in Chinese FDI encourages employment, provides opportunities for the transfer of technology and knowledge. However, other issues arise, such as competition for local entrepreneurs and concerns about Indonesia's economic dependence on China.Besides, to get a comprehensive understanding of Chinese Industrial parks and their impact, future research with field survey research is highly recommended).